Case Series: Efficacy and Safety of Hemoadsorption With HA-330 Adsorber in Septic Pediatric Patients With Cancer - Sazonov, Vitaliy; Abylkassov, Ramazan; Tobylbayeva, Zaure; Saparov, Askhat; Mironova, Olga; Poddighe, Dimitri (Frontiers in Pediatrics, 2021)
Background. Sepsis is a frequent cause of death in hospitalized patients and, in detail, in neonatal, pediatric and adult intensive care units (ICUs). Severe sepsis has a very poor prognosis: indeed, the mortality rate varies between 30-70% during the first 7-14 days. Despite a timely and appropriate therapy, the prognosis of severe sepsis is too often negative. Therefore, new therapeutical resources are under investigations in order to further improve the prognosis. Case series. Here we reported 3 septic children in whom we used extracorporeal blood purification therapy with hemadsorption device HA330 (Jafron Biomedical Co., Ltd, China), aiming to scavenge and eliminate bacterial toxins and inflammatory mediators from the blood. Discussion and Conclusion. This small case series first showed that the hemoperfusion with HA330 cartridge may be an effective and relatively safe adjunctive treatment to counterbalance the cytokine storm in septic children with hematological disorders. Further studies are needed to confirm and further support its safety and efficacy in a large number of pediatric patients.